Clinical Utility of Serum Periostin as Biomarker of Differential Diagnosis for Different Phenotypes of Bronchial Asthma: Serum Periostin as Biomarker for the Diagnosis of Asthma - Rashid, Haji Muhammad; Khan, Mudassar; Khan, Jamal; Sujjad, Muhammad Aamer; Hassan, Hiza; Khan, Hasanat; Abbasi, Mehreen Akhlaq (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
Periostin is a protein produced from epithelial cells of the respiratory tract in response to the stimulation from IL-I3. Periostin levels in serum are associated with its production in airways. This study was conducted to evaluate the clinical utility of serum periostin levels in the differential diagnosis of atopic and non-atopic asthma. This cross-sectional comparative study was carried out at Medsol Clinical Laboratory, Islamabad on 40 healthy individuals as control (Group A) and 40 asthmatic patients (Group B) from Jan-2020 to Aug-2020. Group B was comprised of 20 atopic asthmatic patients (Group BI) with positive skin prick test and 20 non-atopic asthmatic patients (Group BII) with negative skin prick test. Demographic data were obtained on proforma, lung function test and skin prick test was performed at pulmonologist clinic. EDTA and clotted blood samples were obtained from all participants to measure absolute eosinophil count (AEC) and periostin levels. Serum periostin levels were significantly higher in asthmatic patient Group B (396 ± 84) than healthy controls Group A (185 ± 40). In asthmatic groups, serum periostin levels were significantly higher in group BI (atopic asthmatic) than group B II (non-atopic asthma). There was a strong association between serum periostin and AEC (0.83), serum periostin, and FEV1 (-0.81) in atopic asthmatic patients. We concluded that serum periostin can be used for the diagnosis of bronchial asthma and a good purposed biomarker for differential diagnosis of different phenotypes of asthma.